KANDUNGAN PROTEIN KASAR, SERAT KASAR DAN ENERGI FORMULASI RANSUM BURUNG PUYUH PETELUR YANG DITAMBAH TEPUNG DAUN KELOR (Moringa oleifera Lam.) - Rini Andriani; syahruddin syahruddin; Syukri I Gubali; Muhammad Sayuti (xxxx-xxxx, 2022)
This present research aims to analyze and determine the crude protein, crude fiber, and energy contents of the quail ration formulation added with Moringa leaf flour. The raw material for the ration is Moringa leaf flour, while the basic ingredients of feed are milled corn, concentrate, rice bran, fish meal, and premix. The method used is a completely randomized design with 5 treatments and 4 replications. The research finding indicates that the addition of Maringa leaf flour up to a level of 8% in the ration does not have a significant effect (P0.05) on the contents of crude protein, crude fiber, and energy. It can be concluded that Moringa leaf flour can be added up to a level of 8% in the feed ration of laying quail.